THU0526 Efficacy and Safety of Febuxostat in 73 Gouty Patients with Stage 4/5 Chronic Kidney Disease: Result from A Retrospective 9 Multicenter Study. (15th July 2016) - Juge, P.-A.; Truchetet, M.-E.; Pillebout, E.; Ottaviani, S.; Vigneau, C.; Loustau, C.; Cornec, D.; Pascart, T.; Snanoudj, R.; Bailly, F.; Schaeverbeke, T.; Saraux, A.; et al.
Abstract : Background: Although allopurinol reminds the first urate lowering therapy (ULT), its limited dosage in gouty patients with stage 4 or 5 chronic kidney disease (CKD 4/5) prevents to achieve serum uric acid (sUA) level target (<60 mg/l). Febuxostat is a nonpurine xanthine oxidase inhibitor with predominant hepatic metabolism and can be used without dosage adaptation in gouty patients with CKD. However, its safety and efficacy in advanced CKD have been reported in only one study and no data was available in patients with kidney transplantation. Methods: In this retrospective 9 multicenter study, clinical records of all gouty patients with estimated glomerular filtration rate (eGRF) ≤30 ml/min/1.73 m 2 (MDRD formula) at febuxostat initiation and at least 3 month-long follow-up period were selected. Items to collect (demographic data, co-morbidity, renal disease, gout history and former treatments, increasing serum urate drugs, laboratory data and any adverse effects-AEs) were approved by all participant centers. Analysis variables were: sUA level at initiation and last available sUA level; variation of eGFR; the percentage of patients who achieved sUA level <60 mg/l and 50 mg/l; and all AEs with specific attention to cardiovascular events. Results: Seventy-three gouty patients (mean age 70.19 ± 11.84, 61 men) from 9 french different rheumatology and nephrology departments were included. 31 patients (41.47%) suffered from vascular CKD and 18 patients (24.66%) had had renal transplant. Mean duration of gout was 6 years. 32 patients (43.48%) had tophi, 28 (38.36%) gout arthropathies. Diuretics were used in 57 patients (78.08%). Cardiac dysfunction was present in 9 patients (16.4%). 72 patients had hypertension, 22 diabetes melitus, 48 dyslipidemia, 28 (38.36%) had past history of vascular events (stroke, heart infraction). Mean sUA level and eGFR at febuxostat initiation were 98.6 ± 28.5 mg/L and 21.5 ± 6.2 ml/min (6–30ml/min), respectively. Febuxostat initiation dosage was 80 mg daily for 47 patients (68.12%), 80mg every 2 days for 17 patients (24.64%) and 120 mg daily for 5 patients (7.25%). At the last visit (mean follow-up was 68.4 weeks (12–260)) mean sUA level was 50.5 mg/L ± 23.3. Forty-seven patients (64.38%) achieved sUA level target <60 mg/L and 42 (57.53%) had sUA level ≤50 mg/L. Renal function improved in 16 patients (23.88%), was unchanged in 20 (29.85%) and worsened in 31 (46.27%). 18 patients experienced flares under febuxostat treatment. AE was observed in 1 patient who had suffered from limb edema. No cardiovascular event was reported during the time of the febuxostat treatment. Conclusions: Febuxostat appears efficient in gouty patents with stage 4/5 CKD or renal transplants. However, safety data is not clear regarding renal function. Further studies with larger sample are warrant to assess this point. Disclosure of Interest: None declared